48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Source Redistribution on Jet Noise Shielding

Abstract: The potential of jet noise shielding from the Hybrid Wing Body (HWB) airplane is investigated in subscale experiments. The jet nozzle had a bypass ratio 10 and was operated at realistic takeoff exhaust conditions using helium-air mixtures. The shield, fabricated from a thin flat plate, had the generic shape of the HWB planform. Redistribution of the jet noise source is essential for achieving substantial noise reduction. Devices used to alter the jet noise source comprised chevrons (in mild and aggressive conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Brooks and Hodgson evaluated several theories for the case of a two-dimensional airfoil [12] while Howe considered, experimentally, how the shape of the trailing edge influences the noise created [13,14]. More recently, Mayoral and Papamoschou have used experiments to study the potential for increasing jet noise shielding by redistributing the noise sources via chevron nozzles [15] and to examine jet noise shielding in a hybrid wing-body aircraft [16], Hutcheson and Brooks considered the effect of the angle of attack on trailing edge noise [17], and Lawrence et al [1] acquired near-and far-field data for a round jet near a flat surface to validate Amiet's trailing edge noise prediction method and the classically derived scaling exponents. The current Jet-Surface Interaction Tests are an effort to build on these experiments to cover a wider range of surface positions, jet flow conditions, and, in future phases, geometries.…”
Section: Introductionmentioning
confidence: 96%
“…Brooks and Hodgson evaluated several theories for the case of a two-dimensional airfoil [12] while Howe considered, experimentally, how the shape of the trailing edge influences the noise created [13,14]. More recently, Mayoral and Papamoschou have used experiments to study the potential for increasing jet noise shielding by redistributing the noise sources via chevron nozzles [15] and to examine jet noise shielding in a hybrid wing-body aircraft [16], Hutcheson and Brooks considered the effect of the angle of attack on trailing edge noise [17], and Lawrence et al [1] acquired near-and far-field data for a round jet near a flat surface to validate Amiet's trailing edge noise prediction method and the classically derived scaling exponents. The current Jet-Surface Interaction Tests are an effort to build on these experiments to cover a wider range of surface positions, jet flow conditions, and, in future phases, geometries.…”
Section: Introductionmentioning
confidence: 96%
“…Notice that the errors ε k [1] and ε k [2] cannot be determined since the stencil contains points outside the domain of the complex envelope. For an order k, the matrix on the left hand side is a sparse band matrix (tridiagonal matrix in this example) with dimensions of (N − p) × N , p being the number of the filter poles (p = 2 in this example).…”
Section: B Structural Equationmentioning
confidence: 99%
“…The rapid-prototyping approach has been used successfully with jet noise testing of realistic nozzle configurations and open-rotor spinning at full-scale tip speed powered by high-performance DC motors. 2,5 More recently, assessments of the relevance of UCI's small scale ducted fan indicate that small-scale models reproduce with good fidelity the main acoustic features 16 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current century, experimental and theoretical investigations were performed for clarifying features of shielding effect. [4][5][6][7][8][9] In particularly, recent experiments showed that the effectiveness of shielding effect is substantially smaller then predicted in some early works. 4,5 In theoretical works the applications of different diffraction methods were under consideration also, however, the shielding effect was mainly considered for point sources.…”
Section: Introductionmentioning
confidence: 99%